Biomimetic plant foods: Structural design and functionality. (December 2018) - Do, Duc Toan; Singh, Jaspreet; Oey, Indrawati; Singh, Harjinder
Abstract: Background: The rising number of people living with chronic conditions, such as diabetes and cardiovascular disease, along with the widespread demand for healthier foods have posed significant challenges to the food industry. Plant-based foods, beyond simple nutrition, can provide health-benefiting functionalities within the complex environment of the human gastrointestinal (GI) tract. Biomimetics is defined as taking inspirations from nature to solve problems. Biomimetic plant foods (BPFs) can offer solutions for the future with the design of nature-inspired food structures for improved health and well-being. Scope and approach: This review provides an insight into the assembly of plant food structures and their disassembly in the human GI tract. Their role in controlling the digestive fate of nutrients is elucidated. Recent developments and future perspectives on designing BPFs are also presented and discussed. Key findings and conclusions: Plant foods in nature possess hierarchically self-assembled structures. During processing and GI digestion, these structures are disassembled to enable liberation and assimilation of nutrients and bioactive molecules contained within the food matrix. The assembly and disassembly are linked to a hierarchy of structure in plants within which different levels (molecule, polymer, cell wall, cell, tissue, organ) and their interactions can modulate nutrient bioaccessibility and digestion. Inspired by nature, BPFs can be engineered to deliver in-body functionality. The emerging trend of biomimetics will potentially pave the way for the future of food. Highlights: Plant foods are hierarchically assembled in nature. Plant foods are disassembled during processing and digestion in the human body. All hierarchical levels of structure are involved in controlling nutrient digestion. Structural design of plants is a natural template for designing biomimetic foods.